Thirty‐year trends in heart failure hospitalization and mortality rates and the prognostic impact of co‐morbidity: a Danish nationwide cohort study. (11th February 2016) - Schmidt, Morten; Ulrichsen, Sinna Pilgaard; Pedersen, Lars; Bøtker, Hans Erik; Sørensen, Henrik Toft
Abstract : Aims: We examined 30‐year nationwide trends in heart failure hospitalization and mortality rates, and the prognostic impact of co‐morbidity. Methods and results: We conducted a population‐based cohort study of 317 161 patients with first‐time inpatient hospitalizations for heart failure during 1983–2012. We computed the standardized hospitalization rate and 5‐year mortality risk. Co‐morbidity levels and calendar periods of diagnosis were compared by means of mortality rate ratios (MRRs) based on Cox regression. The standardized hospitalization rate (per 100 000 persons) decreased between 1983 and 2012 by 25% for women (from 192 to 144) and by 14% for men (from 217 to 186). The decrease reflected an average annual 1% increase until 2000 and a 3.5% decline thereafter. Between 1983–1987 and 2008–2012, 1‐year mortality declined from 45% to 33% and 1‐ to 5‐year mortality from 59% to 43%. The decline occurred independently of patients' co‐morbidity levels. Comparing 2008–2012 with 1983–1987, the 5‐year age‐, sex‐, and co‐morbidity‐adjusted MRR was 0.57 [95% confidence interval (CI) 0.56–0.58]. Using low co‐morbidity as reference, the adjusted 5‐year MRR in 2003–2007 was increased by 43% for moderate, 66% for severe, and 2.2‐fold for very severe co‐morbidity. The magnitude of co‐morbidity‐associated mortality increased over time and was highest in the youngest patients. Conclusions: Hospitalization rates for heart failure have declined markedly since 2000 in Denmark. One‐ and five‐year mortality declined >40% over the last three decades. The decline in mortality occurred for patients with all levels of co‐morbidity, but co‐morbidity burden was a strong prognostic factor.